Eastern Africa - A study of the Regional Maize Market and Marketing Costs - World Bank (World Bank, 2012)
Maize is the most important staple food in the Eastern Africa region and the most widely traded agricultural commodity. Therefore, the performance of grain markets has a significant impact on people's welfare, particularly the poor, and is critical to inducing pro-poor growth in Kenya, Tanzania, and Uganda, i.e. the countries under review in this report. Marketing costs at the borders would need to be reduced but even more attention should be paid to domestic marketing costs. Policy makers in East Africa should not be misled that encouraging greater regional trade is solely a diplomatic matter. Instead, concerted public investments and policy actions at local, national, and regional levels are required. Reduced marketing costs would allow a reduction in input prices and thus production costs. This report aims to examine, identify, and quantify the factors behind the marketing costs for maize in East African countries. While a number of studies have recognized major barriers to trade in the region, few have actually quantified their relative importance or the magnitudes of these constraints on grain trade. Since much past research has been inconclusive, a key focus of this report is to identify how different barriers contribute to marketing costs within countries and across borders. It also aims to analyze whether a reduction in cross-border trade costs without a simultaneous reduction in domestic costs would be sufficient for greater regional integration in East Africa.